Using fracture scarp intersection lineations as kinematic indicators on active normal fault scarps - Billy J. Andrews; Zoë K. Mildon; Manuel L. Diercks; Sam Mitchell; Gerald P. Roberts; Constanza Rodriguez Piceda; Jenni Robertson (Journal of Structural Geology, 2026)

Environmental Drivers of Recruitment Variability in Narrow‐Barred Spanish Mackerel Scomberomorus commerson Lacépède, 1800 - Susannah M. Leahy; Joanne Langstreth; Rik C. Buckworth; Peri Subritzky; Olivia J. Whybird; Sam M. Williams; Lucas I. Sumpter; Jonathan D. Mitchell (Fisheries Oceanography, 2026)
Understanding the effects of environmental conditions on fisheries resources is crucial for guiding the effective assessment and management of fish stocks. Previously assessed as depleted, the narrow‐barred Spanish mackerel fishery on the east coast of Queensland, Australia, is under management intervention to rebuild the stock. In this study, we use long‐term age composition data to reconstruct 24 years of historic year class strength and explore a broad range of potential environmental influences on recruitment variability in the fishery. Year class strength was extremely well captured (76%–84% deviance explained) by generalised additive models containing just four environmental indices. Recurring key environmental indices in top models included environmental conditions prior to spawning (large scouring flood events during the wet season before spawning and cool winter sea surface temperature immediately prior to spawning), during spawning (unseasonal flooding near the spawning grounds), during larval dispersal and proxies for food availability for juvenile Spanish mackerel. These results have since been used to hindcast recruitment variability in the fishery prior to the collection of the age‐composition data to better understand historic fluctuations in the fishery, and can also be incorporated into management strategies for rebuilding the stock.

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Multi-millennia slip rate relationships between closely spaced across-strike faults: Temporal earthquake clustering of the Skinos and Pisia Faults, Greece, from in situ 36Cl cosmogenic exposure dating - Sam Mitchell; Claudia Sgambato; Jenni Robertson; Gerald P. Roberts; Joanna P. Faure Walker; Zoë Mildon; Athanassios Ganas; Ioannis Papanikolaou; Francesco Iezzi; Joakim Beck; Steven A. Binnie; Tibor Dunai; et al. (Journal of Structural Geology, 2025)

Does Home and Wild Food Procurement Enhance Food Security in High-Income Countries? - Sam Bliss; Ashley C. McCarthy; Rebecca C. Mitchell; Scott C. Merrill; Rachel E. Schattman; Janica Anderzén; Meredith T. Niles (Current Environmental Health Reports, 2025)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

The relationship between kinematics and fault geometry for surface coseismic ruptures on across-strike faults: New observations of slip vectors and displacements along the Pisia and Skinos faults from the 1981 Eastern Gulf of Corinth, Greece earthquakes - Sam Mitchell; Gerald P. Roberts; Joanna P. Faure Walker; Francesco Iezzi; Claudia Sgambato; Jennifer Robertson; Zoë K. Mildon; Athanassios Ganas; Ioannis D. Papanikolaou; Elias J. Rugen (Journal of Structural Geology, 2024)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Mapping of the stem rust resistance gene Pg13 in cultivated oat - Aida Z. Kebede; Belayneh Admassu-Yimer; Wubishet A. Bekele; Tyler Gordon; J. Michael Bonman; Ebrahiem Babiker; Yue Jin; Sam Gale; Charlene P. Wight; Nicholas A. Tinker; Jim G. Menzies; Aaron D. Beattie; et al. (Theoretical and Applied Genetics, 2020)

The Business of Forest Enterprise / Urban Ecosystems - Steve Narolski; Richard Bin Mei; Rafael De La Torre; Mike Clutter; John Pait; Maggi Kelly; Frederick Cubbage; Patricio MacDonagh; Gustavo Balmelli; Virginia Morales Olmos; Adriana Bussoni; Rafael Rubilar; et al. (Journal of Forestry, 2011)
22In 2009, five unique methods were used to inspect vegetation-related conditions along Bonneville Power Administration (BPA) rights-of-way (ROW). Some methods were trials that BPA committed to execute as part of a settlement with its regional regulatory organization, the Western Electric Coordination Council (WECC), for violations of reliability standards from vegetation grow-in related outages. A combination of simple, stratified, and 100% sampling were used to compare and contrast each inspection technique. A cost-replacement comparison between all inspection techniques was performed, weighting efficacy of one technique to another in the form of replacement value. Cost-benefit and return-on-investment analyses were also computed. From these analyses, LiDAR proved most effective in identifying vegetation related clearance issues but proved most costly, at least for initial establishment. The average cost of LiDAR trended downward with subsequent flights. The most cost effective method was using helicopters with either Natural Resource Specialists (NRS) or Transmission Line Maintenance (TLM) personnel serving as aerial observers, but this methodology proved the most inaccurate. Furthermore, the ancillary utility of LiDAR for related asset assessments more than justify the initial expense, includes power line sag ratings, asset (structures, insulators, roads, etc.) health, and encroachment identification. It is hypothesized that incorporating LiDAR sampling from 20% of the whole system per year to 40+ % may actually represent a cost-savings when allocating available resources system-wide. This data can also be used for documenting compliance with all federal regulations and requirements, as well as substitute for manual on-the-ground inspections, whether by BPA staff or third-party contractors.